Предмет: Математика,
автор: хай62
решите уравнение
-2х²-5х+3=0
Ответы
Автор ответа:
0
Обе части уравнения умножим на - 1
2х^2 + 5x - 3 = 0
D = 25 - 4 *(- 3) * 2 = 25 + 24 = 49 √D = 7
x1 = ( - 5 + 7) / 4 = 1/2
x2 = ( - 5 - 7) / 4 = - 3
2х^2 + 5x - 3 = 0
D = 25 - 4 *(- 3) * 2 = 25 + 24 = 49 √D = 7
x1 = ( - 5 + 7) / 4 = 1/2
x2 = ( - 5 - 7) / 4 = - 3
Автор ответа:
0
Домножим на (-1) получается:
2x^2+5x-3=0
D=5^2-4*2*(-3)=25+24=49
X1=-5+7/4=2/4=0,5
X2=-5-7/4=-12/4=-3
Ответ:X1=0,5;X2=-3
2x^2+5x-3=0
D=5^2-4*2*(-3)=25+24=49
X1=-5+7/4=2/4=0,5
X2=-5-7/4=-12/4=-3
Ответ:X1=0,5;X2=-3
Похожие вопросы
Предмет: История,
автор: gurinovichr54
Предмет: Информатика,
автор: vcecam
Предмет: Математика,
автор: imakienkova
Предмет: Алгебра,
автор: Аноним